Exclusive Breastfeeding and Complementary Feeding on Stunting Children Among 12-24 Months: A Retrospective Study - Dewi Modjo; Zuriati Muhamad; Aurelia Intan Sitty Aisyah P.S.P Oei (Biology, Medicine, & Natural Product Chemistry, 2025)
This study aimed to analyze the relationship between the exclusive breastfeeding and complementary feeding, as well as the incidence of stunting in children between the ages of 12-24 months. An observational analytical study design with a cross-sectional approach was applied to examine the relationship between independent variables (knowledge of exclusive breastfeeding and complementary feeding) and the dependent variable (stunting). This study was conducted in the working area of the Kota Tengah Health Center working area. The results showed significant relationship between exclusive breastfeeding and the incidence of stunting in children (r: 0.541) with a p-value of 0.000 (p-value < 0.05), as well as a significant relationship between complementary feeding and the incidence of stunting in children (r: 0.332) with a p-value of 0.000 (p-value < 0.05). This study provides valuable information to mothers, highlighting the causes of stunting and promoting preventative measures to minimize its occurrence, such as carrying out consultations at the health care centre with personnel or professionals and addressing cases promptly.